Spatial metatranscriptomics resolves host-bacteria-fungi interactomes, Source Data - Saarenpää, Sami; Shalev, Or; Ashkenazy, Haim; Carlos, Vanessa; Lundberg, Derek Severi; Weigel, Detlef; Giacomello, Stefania (Royal Institute of Technology, 2023)
Source Data for a publication: Spatial metatranscriptomics resolves host-bacteria-fungi interactomes.

Includes the data sets to generate the results.

Contains five different experiment types:

- Pst  bacterial infiltration experiment
- Enrichment experiment with different array types
- Comparison between SmT vs. Amp-seq
- Outdoor-grown leaf experiments
- Sterile leaf experiment

For each of the experiments are included (if generated, see the README file):
- Gene count matrices
- Microbial taxa count matrices
- Bright field images
- Alignment files (Spot files)
- Putative microbial reads and related probe information
- Data for enrichment analysis
- Fluorescent images and corresponding fluorescent values
Keywords: Spatial Transcriptomics; Spatial metaTranscriptomics; Transcriptomics; Microbe; Host-microbe interactions; Microbiology; Mikrobiologi